Large enhancement of discharge energy density of polymer nanocomposites filled with one-dimension core-shell structured NaNbO3@SiO2 nanowires. (June 2020) - Chen, Jianwen; Ye, Dagui; Wu, Xiaowei; Zhu, Wenbo; Wang, Xiucai; Xiao, Peng; Duan, Zhikui; Yu, Xinmei
Highlights: The large-aspect-ratio 1D NaNbO3 nanowires are prepared via a simple hydrothermal method method. Nanocomposite films filled with 3 vol% NN@SiO2 NWs show a large discharged energy density of 12.1 J cm −3 at 430 MV m −1, which is ≈ 243% over the bare PVDF (4.98 J cm −3 at 350 MV m −1 ) and ≈1008% greater than biaxially oriented polypropylenes (BOPP) (≈1.2 J cm −3 at 640 MV m −1 ). Finite element simulation confirms the superiority of the 1D core-shell structured NN@SiO2 NWs in improving the energy density of the nanocomposite films. Abstract: Design an architecture with the ability to improve breakdown strength has critical role to play for performance enhancement in energy storage capability. In this work, we report that the composite films with loaded with one dimension (1D) core-shell structured NaNbO3 @SiO2 nanowires (NN@SiO2 NWs) are prepared and achieved significantly performance improvement in energy storage capability. The finite element simulation and experiment results both confirm the superiority of the 1D core-shell structured NN@SiO2 NWs in improving the energy density of the nanocomposite films. Especially, the nanocomposite films filled with 3 vol% NN@SiO2 NWs show a large discharged energy density of 12.1 J cm −3, which is ≈ 243% over the bare PVDF (4.98 J cm −3 ) and ≈ 1008% greater than biaxially oriented polypropylenes (BOPP) (≈ 1.2 J cm −3 at 640 MV m −1 ). Therefore, this nanocomposite film can be considered as potential high-performance dielectric materials for next-generation pulsed power capacitor applications.